Essentials of Business Law and the Legal Environment - Mann, Richard A (Thomson, 2007)
This book is continous the tradition of accuracy, comprehensiveness, and authoritativeness associated with its earlier editions.This text covers its subject material in a succinct, nontechnical but authoritative manner, and provides depth sufficient to ensure easy comprehension by today's students.This text is design for use in business law and legal environment courses generally offered in universities, colleges, and schools of business and management. Because of its broad coverage and variety of the material, this text may be readily adapted to specially design in business law.